1903 Or. Special Laws 31, An Act to Incorporate the City of Portland, ch. 3, art. 4,§§§73, pt. 38. - (:unkn) unknown (My University, 1903)
To regulate and prohibit the use of all guns, pistols, and firearms, missle [sic] weapons, firecrackers, bombs and detonators of all description[.]
Keywords: DISCHARGE